2016
DOI: 10.1111/jmft.12169
|View full text |Cite
|
Sign up to set email alerts
|

Unique Characteristics of Cohabiters Seeking Therapy

Abstract: There is limited information on cohabiters presenting for therapy. The authors examined the characteristics of 143 married and 54 cohabiting, young (m = 30.39), Caucasian, couples presenting for therapy. We hypothesized that cohabiters presenting for therapy would be more satisfied and committed than married couples and that they would be similarly emotionally differentiated. We conducted a repeated-measures MANOVA to test the hypothesis. Significant effects between partners and between dyads were found, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
1
Order By: Relevance
“…In the final two-class solution, those who were married were more likely to be in the female low increasing and male mid-stable class versus those who were dating or cohabiting. It may be that those who seek services who are dating or cohabiting find a decline in satisfaction to be more threatening and so seek services sooner than married couples seeking services (Shannon & Bartle-Haring, 2017). Married couples were more likely to be in Class 1, present to therapy with lower levels of satisfaction, and show more improvement overall, which has been documented in other studies as well (e.g., Roddy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the final two-class solution, those who were married were more likely to be in the female low increasing and male mid-stable class versus those who were dating or cohabiting. It may be that those who seek services who are dating or cohabiting find a decline in satisfaction to be more threatening and so seek services sooner than married couples seeking services (Shannon & Bartle-Haring, 2017). Married couples were more likely to be in Class 1, present to therapy with lower levels of satisfaction, and show more improvement overall, which has been documented in other studies as well (e.g., Roddy et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Married couples, on the other hand, tend to seek services when their level of satisfaction with the relationship is much lower. Shannon and Bartle-Haring (2017) suggested that since marriage comes with a legal status, there are more barriers to break up and thus less satisfaction in the relationship can be tolerated in comparison to relationship statuses that have no legal status. Although the legal status of marriage may make it seem more enduring, it seems to lead couples to tolerate lower levels of satisfaction before seeking services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudios recientes indican que empezar a cohabitar facilita que los individuos desarrollen compromiso hacia su pareja y una perspectiva sobre su futuro, que genera conductas de planeación económica (Fulda & Lersch, 2018). Por otra parte, al enfrentar problemas en su relación, las parejas que cohabitan buscan ayuda terapéutica más pronto que las casadas y demuestran mayor compromiso hacia su relación (Shannon & Bartle-Harring, 2016). Estos estudios sugieren que existen aspectos positivos en las relaciones de parejas que cohabitan que deben ser examinados.…”
Section: Compromisso Autorregulação E Intimidade Em Casais Em Coabitunclassified